2021
DOI: 10.1111/ijpo.12841
|View full text |Cite
|
Sign up to set email alerts
|

Youth prediabetes and type 2 diabetes: Risk factors and prevalence of dysglycaemia

Abstract: Background: The American Diabetes Association recommends risk-based screening for dysglycaemia (prediabetes and type 2 diabetes) in youth with overweight/obesity plus ≥1 risk factor. However, evidence for these recommendations is lacking.Objectives: Examine the association between the number of risk factors and the prevalence of dysglycaemia in youth with overweight/obesity at initial presentation.Methods: In a paediatric obesity registry, youth (>10 and <20 years old, body mass index ≥85th percentile) were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
13
0
1
Order By: Relevance
“…Today, prediabetes is on the rise along with diabetes [ 20 ]. Controlling blood sugar has reduced mortality and increased life expectancy, but there are still many patients who suffer from long-term complications of the disease, so, preventing pre-diabetes to diabetes is more important to prevent chronic complications [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, prediabetes is on the rise along with diabetes [ 20 ]. Controlling blood sugar has reduced mortality and increased life expectancy, but there are still many patients who suffer from long-term complications of the disease, so, preventing pre-diabetes to diabetes is more important to prevent chronic complications [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Indeed, the prevalence of dysglycemia, escalated from ~23% in youth with overweight and one risk factor to up to ~45% in youth with ≥4 risk factors. 6 In line with current guidelines for screening, 5 most of the studies have investigated prevalence of dysglycemia in children older than 10 years old. Analysis of data from the National Health and Nutrition Examination Survey from 1999 through 2012 demonstrated that prevalence of IFG and prediabetic HbA1c increased with worsening of obesity from overweight to class III obesity in adolescents older than 12 years old.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018 the American Diabetes Association (ADA) made the recommendation to screen for prediabetes all youth with overweight at 10 years of age or above with one or more of risk factors among nonwhite race, family history of type 2 diabetes (T2D) in first or second degree relatives, maternal gestational diabetes, or signs of insulin resistance, specifically acanthosis nigricans, hypertension, dyslipidemia, polycystic ovarian syndrome or small‐for‐gestational age birth weight 5 . Indeed, the prevalence of dysglycemia, escalated from ~23% in youth with overweight and one risk factor to up to ~45% in youth with ≥4 risk factors 6 …”
Section: Introductionmentioning
confidence: 99%
“…Several factors may be involved in the anticipation of T2D onset, although the dramatic increase in childhood and adolescent obesity worldwide plays a key role in this process [5]. Similarly, the condition of prediabetes in youth has risen steeply worldwide in parallel with rising rates of obesity [6]. In the National Health and Nutrition Examination Survey cohort database, 13.1% of United States adolescents had impaired fasting glycemia, and 3.4% had impaired glucose tolerance after oral glucose load.…”
Section: Introductionmentioning
confidence: 99%